2013
DOI: 10.1037/a0032601
|View full text |Cite
|
Sign up to set email alerts
|

Religious behavior, health, and well-being among Israeli Jews: Findings from the European Social Survey.

Abstract: This study investigates the relationship between religious behavior and health status and psychological well-being in a population sample of Israeli Jewish adults (N ϭ 1,849). Using data from the Israeli sample of the European Social Survey, measures of synagogue attendance and private prayer were examined in relation to single-item indicators of subjective and functional health, happiness, and life satisfaction and to a three-item scale tapping into the somatic dimension of well-being. Bivariately, the religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 78 publications
(75 reference statements)
2
23
0
Order By: Relevance
“…The research presented adds to the literature on the connection between religion and health. In addition to providing additional evidence that bears on differing results from prior studies (Shmueli, 2006;Levin, 2013), this paper is among the few to study the relationship between religious "degree" and health status. Use of five categories 11 representing a continuum of religiosity from secular to very devoutly religious and analyzing them across a range of subjective and physical and mental health measures is, to our knowledge uncommon and an important contribution to research about Israeli Jews and their health.…”
Section: Contributions Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…The research presented adds to the literature on the connection between religion and health. In addition to providing additional evidence that bears on differing results from prior studies (Shmueli, 2006;Levin, 2013), this paper is among the few to study the relationship between religious "degree" and health status. Use of five categories 11 representing a continuum of religiosity from secular to very devoutly religious and analyzing them across a range of subjective and physical and mental health measures is, to our knowledge uncommon and an important contribution to research about Israeli Jews and their health.…”
Section: Contributions Of the Studymentioning
confidence: 98%
“…A study using some measures of self-reported health and quality of life found increased religiosity to be associated with poorer health (Shmueli 2006; another study found that religious Israeli Jews also generally have better results than less religious Israeli Jews in terms of health behaviors and preventive screenings performed (Shmueli and Tamir 2007). A more recent study of Israeli Jews found generally, but not always, salutary results between measures of religious behaviors and health and well-being outcomes (Levin 2013). Studies of U.S. Jews have revealed a positive health impact of religious identity and participation (Levin 2011;Levin 2015); Using American denominational categories, Orthodox Jews who attend synagogue typically were found to have better self-rated health status than Conservative, Reform and Reconstructionist Jews , even among those who attended synagogue.…”
Section: Prior Research and Study Importancementioning
confidence: 99%
“…Moreover, using religion and trust in God for coping with difficult events were related to lower depression and anxiety (Krumrei, Pirutinsky, & Rosmarin, 2013; Rosmarin, Pargament, & Mahoney, 2009). Research on the Jewish-Israeli population found that religiosity, measured with different indicators, is linked to better life satisfaction (Levin, 2012b, 2013c), less stress and a healthier life style (Shmueli & Tamir, 2007), better well-being (Levin, 2011, 2013b) and happiness (Levin, 2013b, 2014). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Adjusting for effects of this variable is thus valuable in ruling out that any putative significant findings may be due in part to the nativity of respondents. Controlling for effects of such a variable has proven useful in previous studies in this literature (e.g., [37,39,40]). …”
Section: Covariatesmentioning
confidence: 99%
“…So far, this project has identified significant effects of Jewish religious observance on self-rated health and presence of an activity-limiting health condition in the U.S. [34], on happiness and life satisfaction in Israel and in the diaspora [35], and on psychological well-being and psychological distress [36], health and well-being [37], happiness [38], and numerous measures of physical and mental health [39,40] in Israel. For the most part, though not exclusively, greater religiousness is associated on average with better health and well-being and less psychological distress.…”
Section: Judaism and Well-beingmentioning
confidence: 99%